2012
DOI: 10.1016/j.brainres.2012.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Understanding tinnitus: The dorsal cochlear nucleus, organization and plasticity

Abstract: Tinnitus, the perception of a phantom sound, is a common consequence of damage to the auditory periphery. A major goal of tinnitus research is to find the loci of the neural changes that underlie the disorder. Crucial to this endeavor has been the development of an animal behavioral model of tinnitus, so that neural changes can be correlated with behavioral evidence of tinnitus. Three major lines of evidence implicate the dorsal cochlear nucleus (DCN) in tinnitus. First, elevated spontaneous activity in the DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 140 publications
(198 reference statements)
0
53
0
3
Order By: Relevance
“…This suggests that neuroplastic changes could be responsible for long-term alterations and the persistence of tinnitus in the chronic condition [15]. Previous research has demonstrated that a reorganisation of the DCN occurs following acoustic trauma [3]. These plastic changes could be a response to a new equilibrium being established as communication is altered from the auditory periphery [8].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This suggests that neuroplastic changes could be responsible for long-term alterations and the persistence of tinnitus in the chronic condition [15]. Previous research has demonstrated that a reorganisation of the DCN occurs following acoustic trauma [3]. These plastic changes could be a response to a new equilibrium being established as communication is altered from the auditory periphery [8].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, evidence of reduced GABAergic inhibition and increased spontaneous activity has also been found in the dorsal cochlear nucleus (DCN) of mice with behaviour signs of tinnitus [11]. Since the CN is the first region of the CNS to receive and process auditory information, it occupies an pivotal role in the generation of tinnitus [3]. The dorsal cochlear nucleus (DCN), especially, has been proposed as a tinnitus trigger site [7].…”
Section: Introductionmentioning
confidence: 99%
“…There are several lines of evidence that implicate the DC in tinnitus. These include: (1) the presence of elevated spontaneous activity in the DC which is correlated with peripheral damage and tinnitus; (2) the somatosensory inputs to the DC that can modulate spontaneous activity and might mediate the somatic-auditory interactions seen in tinnitus patients; and (3) the expression of doublecortin, a plasticity-related protein (for review, see Baizer et al, 2012). Recent data also implicate the VC, and in particular spherical bushy cells in tinnitus (Gu et al, 2012).…”
Section: Functional Significance Of the DC Circuitrymentioning
confidence: 99%
“…The cochlear group of nuclei constituent an important part of the auditory brainstem system which is critical for sound localization/processing and has been implicated in hearing disorders such as tinnitus [15]. Projections from the dorsal cochlear nuclei (DCN) in particular, have been demonstrated after retrograde tracer injection into the posterior vermis [16].…”
Section: Resultsmentioning
confidence: 99%